Pengaruh Aplikasi Pupuk EM4 Komersil Dan EM4 Kulturisasi Pada Pertumbuhan Tanaman Sawit - Nina Veronika (Jurnal Sains dan Ilmu Terapan, 2018)
The use of chemical fertilizers that are not equalized with organic fertilizers can damage the soil fertility and it is not environmentally friendly, because the microorganisms which have a role in decompose process will not develop. On the other hand, the high prices of organic fertilizers make farmers reluctant to use organic fertilizers. To solve this problem, farmers could be used microorganism with culturing process. The purpose of this research is to determine the comparison of EM4 with culturing process and EM4 in commercial liquid organic fertilizer that applied in mustard plants.